2021
DOI: 10.1097/ccm.0000000000005299
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Life Support for Respiratory Failure in Patients With Electronic Cigarette or Vaping Product Use–Associated Lung Injury

Abstract: Electronic cigarette or vaping product use-associated lung injury is a clinical entity that can lead to respiratory failure and death. Despite the severity of electronic cigarette or vaping product use-associated lung injury, the role of extracorporeal life support in its management remains unclear. Our objective was to describe the clinical characteristics and outcomes of patients with electronic cigarette or vaping product use-associated lung injury who received extracorporeal life support. DESIGN:We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…EVALI commonly presents as nonspecific respiratory symptoms (such as cough, dyspnoea and chest pain) often with associated gastrointestinal symptoms, fever, chills and weight loss. However, the syndrome may be severe with catastrophic respiratory failure as a result of a potent inflammatory response to the e-liquid [ 20 ]. It is a diagnosis of exclusion, which requires a history of vaping, the absence of other possible microbiological or other pathological causes, and radiological evidence consistent with EVALI [ 9 , 18 ].…”
Section: Vaping-related Harmsmentioning
confidence: 99%
See 1 more Smart Citation
“…EVALI commonly presents as nonspecific respiratory symptoms (such as cough, dyspnoea and chest pain) often with associated gastrointestinal symptoms, fever, chills and weight loss. However, the syndrome may be severe with catastrophic respiratory failure as a result of a potent inflammatory response to the e-liquid [ 20 ]. It is a diagnosis of exclusion, which requires a history of vaping, the absence of other possible microbiological or other pathological causes, and radiological evidence consistent with EVALI [ 9 , 18 ].…”
Section: Vaping-related Harmsmentioning
confidence: 99%
“…The presentation, radiological findings, clinical course and pathophysiology and histopathology for EVALI is diverse. The condition can be severe, requiring intensive care and in some cases extracorporeal membrane oxygen [ 9 , 18 , 20 , 22 ]. A systematic review has correlated animal and mechanistic studies with human data, and has not identified a single cause, concluding that the condition is likely multifactorial with exogenous and endogenous factors playing a role [ 22 ], which, given the many disparate manifestations of EVALI, is biologically plausible.…”
Section: Vaping-related Harmsmentioning
confidence: 99%